Media Law Handbook - Fernandez, Joseph (Griffin Press, 2007)
Freedom of speech has never been an absolute value in the political and legal landscape - not in Australia, and not anywhere else. Laws on defamation, blasphemy, copyright, obscenity, incitement, secrecy, contempt, racial vilification and sedition are some of the laws that commonly impinge on freedom of speech. These laws exist to protect countervailing interests that may deserve priority over freedom of speech in the event of a conflict between the two. Our laws reflect the belief that the need for social cohesion and the need to maintain public order require limitations on freedom of speech where this freedom may lead to a breach of the peace. It accepts that words, images and information can seriously injure individuals and institutions and their economic and social wellbeing. As more Australian jurisdictions embrace the need for the protection of human rights through charters and similar instruments, freedom of speech - a fragile creature of innovative judicial thinking - is gaining a stronger foothold in the statute books. This text incorporates discussion of recent amendments including the law pertaining to journalists' confidential sources. The Media Law Handbook considers the laws that impact on freedom of speech and is an essential guide for journalists and other engaged in the media.